The Effects of HCl and CaCl(2) Injections on Intracellular Calcium and pH in Voltage-clamped Snail (Helix aspersa) Neurons - Thomas, Roger C. (The Rockefeller University Press, 2002)
To investigate the mechanisms by which low intracellular pH influences calcium signaling, I have injected HCl, and in some experiments CaCl(2), into snail neurons while recording intracellular pH (pH(i)) and calcium concentration ([Ca(2+)](i)) with ion-sensitive microelectrodes. Unlike fluorescent indicators, these do not increase buffering. Slow injections of HCl (changing pH(i) by 0.1–0.2 pH units min(−1)) first decreased [Ca(2+)](i) while pH(i) was still close to normal, but then increased [Ca(2+)](i) when pH(i) fell below 6.8–7. As pH(i) recovered after such an injection, [Ca(2+)](i) started to fall but then increased transiently before returning to its preinjection level. Both the acid-induced decrease and the recovery-induced increase in [Ca(2+)](i) were abolished by cyclopiazonic acid, which empties calcium stores. Caffeine with or without ryanodine lowered [Ca(2+)](i) and converted the acid-induced fall in [Ca(2+)](i) to an increase. Injection of ortho-vanadate increased steady-state [Ca(2+)](i) and its response to acidification, which was again blocked by CPA. The normal initial response to 10 mM caffeine, a transient increase in [Ca(2+)](i), did not occur with pH(i) below 7.1. When HCl was injected during a series of short CaCl(2) injections, the [Ca(2+)](i) transients (recorded as changes in the potential (V(Ca)) of the Ca(2+)-sensitive microelectrode), were reduced by only 20% for a 1 pH unit acidification, as was the rate of recovery after each injection. Calcium transients induced by brief depolarizations, however, were reduced by 60% by a similar acidification. These results suggest that low pH(i) has little effect on the plasma membrane calcium pump (PMCA) but important effects on the calcium stores, including blocking their response to caffeine. Acidosis inhibits spontaneous calcium release via the RYR, and leads to increased store content which is unloaded when pH(i) returns to normal. Spontaneous release is enhanced by the rise in [Ca(2+)](i) caused by inhibiting the PMCA.